RESEARCH OF THE INTELLECTUAL CAPITAL MAIN COMPONENTS OF THE INNOVATIVELY ACTIVE ENTERPRISE - M. Bobrova; L. Mikhailova; A. Sazonov (Вестник университета)
The article opens basic approaches to definition of the intellectual capital in the conditions of innovative economy. The category of the intellectual capital from positions of cause and effect interrelations and interconditionality in development of the enterprise has investigated. Classification of the intellectual capital has given to several main groups from a position of his quality and the size, depending on ability of the enterprise to receive return from the invested capital and on extent of the received return from his use in general.